Education in the Federal District: A left-wing politics? (Andamios, Revista de Investigación Social, 2012)
This article analyzes congruence in the educative policy of the governments postulated by the Partido de la Revolución Democrática (PDR) in the City of Mexico from its arrival in 1997. This party, in center proposed a tie supply with values of left, placing the problem of the inequality of its social policy distinguishing itself in this way of the positions of the federal government. The revision of the conducted battles allows to understand as this educative project has been accompanied by a set of alternatives within the framework of an agreed favorable political conjuncture the left ideology.
Keywords: Educative policy; education; educative fairness; governments of left; political parties in Mexico